Comparison of ultrasound-guided and conventional arthrocentesis of the temporomandibular joint - NAMDAR PEKİNER, FİLİZ MEDİHA; GÖÇMEN, GÖKHAN; ÖZKAN, YAŞAR (CHURCHILL LIVINGSTONE, 2016)
Arthrocentesis of the temporomandibular joint (TMJ) can be done either conventionally or under ultrasonographic guidance, and we have compared the effectiveness of the two techniques. Twenty patients who required arthrocentesis of the TMJ were randomly assigned to ultrasonographically guided (US-guided) and conservative arthrocentesis (n = 10 in each group). The number of relocations of the first and second punctures, pain experienced during each procedure measured using a visual analogue scale (VAS), and the duration of the procedure were the main outcome variables. The pain score compared with the maximal interincis al mouth opening measured preoperatively, immediately after operation, at 1 week, and 1 and 3 months, were secondary outcome variables. No patient in either group developed a complication, and there was no significant difference between the two groups, except that US-guided arthrocentesis took significantly longer than the conventional technique (p = 0.000). US-guided arthrocentesis of the TMJ was no more successful than the conventional technique, and took longer. Further studies with more patients are required to validate these findings. (C) 2016 The British Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Arthrocentesis; Temporomandibular joint; Ultrasonography; CORTICOSTEROID INJECTION; OUTCOMES